Edible Selby - Selby, Todd (Abrams, 2012)
"Photographer Todd Selby is back, this time focusing his lens on the kitchens, gardens, homes, and restaurants of more than 40 of the most creative and dynamic figures working in the culinary world today. He takes us behind the scenes with Noma chef René Redzepi in Copenhagen; to Tokyo to have a slice with pizza maker Susumu Kakinuma; and up a hilltop to dine at an inn without an innkeeper in Valdobbiadene. Each profile is accompanied by watercolor illustrations and a handwritten questionnaire, which includes a signature recipe. Reveling in the pleasures of a taco at the beach, foraging for wild herbs, and the art of the perfectly cured olive, Selby captures the food we love to eat and the people who passionately grow, cook, pour, and serve these incredible edibles every day"--